Approximation of Amplitude Equalizer Based on q-Bessel Polynomials - Janchitrapongvej, Kanok; Rattanathanawan, Pongpan; Chutchavong2*, Vanvisa (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this paper, a method to equalize the amplitude distortion of linear slope signal in waveform transmission is presented. In order to design the linear gain slope amplitude equalizer with maximally flat group delay, a non-minimum phase network technique is utilized. Thus, the transmission zeros possess quadrant symmetry and the denominator of the transfer function is approximated by using q-Bessel polynomials. As it is known, the q-Bessel polynomial has more parameter to adjust than does the simple Bessel polynomials. In order to investigate the performance of the design equalizer. Simulation of the proposed gain slope response is carried out. Moreover, the stability of the approximated transfer function is investigated by using a Mihailov’s criterion. It is shown that the simulation results agree with the theoretical ones. Keywords: q-Bessel Polynomials, non-minimum phase, amplitude equalizer, Mihailov’s criterion. *Corresponding author: E-mail: kcvanvis@kmitl.ac.th